Efficiency of Silver Staining in Differential Diagnosis of Adenoid Cystic Carcinoma from Polymorphous Low-Grade Adenocarcinoma - Valipour Tahamtan, Mahbube; Shahbeik, Shahrzad; Abdollahi, Alireza; Rezvani, Gita (Journal of Dental School, 2019)
Objectives The aim of this study is find a practical and easy way to histologically differentiate between two malignant tumors namely Adenoid Cystic Carcinoma (ACC) and Polymorphous Low-grade Adeno Carcinoma (PLGA) silver nitrate staining. Methods In this cross-sectional study, 30 parrafin-embedded blocks of ACC and nine paraffin-embedded blocks of PLGA with the most acceptable standards were selected and stained with silver nitrate. Then the number and quality (size and pattern) of the stained spots in five random microscopic fields at 100× magnification (at least 100 cells) were evaluated. T-test was used to compare the number of dots between the two tumors while the quality of dots was compared with the Mann-Whitney U test. Results The mean silver stainable nucleolus organizer region (AgNOR) count was 3/45 for ACC and 2/45 for PLGA. Significant differences were observed in the number of dots between ACC and PLGA (p=0.004), but there was no statistically significant difference between the two tumors in terms of quality of dots. Conclusion AgNOR count can be useful as an available method in confirm the diagnosis of ACC and differentiate it from PLGA.